Socioeconomic determinants of obesity and hypertension at the county level in China. Issue 4 (1st October 2016) - Zhang, Tao
ABSTRACT: In a nationally representative database, the risk of obesity and hypertension in China is significantly associated with age and the socioeconomic environment. Women in China are more likely obese and less likely to have hypertension than men. Education mitigates the risks of obesity and hypertension.